Removal of metallic foreign body in heart by minimally invasive procedure under the guidance of transesophageal echocardiography and transthoracic echocardiogram - Qian, Hong; Song, Haibo; Li, Yajiao; Jiang, Chunling (Journal of Thoracic Disease, 2015)
Penetrating cardiac injury, caused by intracardiac foreign bodies, presents a big challenge to surgeons for that it is difficult to exactly locate the intracardiac foreign bodies due to the continuous movement of heart. We present the case of successful removal of two self-inflicted intramyocardial needles by minimally invasive procedures. Under the guidance of transesophageal echocardiography (TEE) and transthoracic echocardiogram (TTE), left mini-anterolateral thoracotomy was performed and the needles were located and removed. The patient was discharged from hospital 5 days after surgery without any complications. In our case, the TTE and TEE provide valuable informations on the choice of surgical procedure, which avoids opening the chest and use of cardiopulmonary bypass (CPB).